In Vitro Comparison of Antifungal Activity between Epigallocatechin Gallate EGCG) and Nystatin on Candida Sp. Stored Isolates in HIV/AIDS Patients with Oral Candidiasis - Wibisono, Yusuf; Hidayati, Afif Nurul; Sawitri, Sawitri; Prakoeswa, Cita Rosita Sigit; Zulkarnain, Iskandar; Ervianti, Evy; Rahmadewi, Rahmadewi; Hendradi, Esti; Endraswari, Pepy Dwi; Murtiastutik, Dwi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Oral candidiasis is an oral infection caused by Candida albicans. It is one of the most common opportunistic infections found in patients with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS). Due to growing resistance and side effects to common antifungal drugs in recent years, there have been many studies on naturalsubstances as antifungal agents. In this study, Epigallocatechin gallate (EGCG) were examined for in vitro antifungal activity against Candida strains. Purpose: To compare the in vitro antifungal activity of EGCG and nystatin towards Candida sp. isolate in HIV/AIDS patients with oral candidiasis. Methods: This research was an experimental laboratory study conducted at the Dr. Soetomo General Academic Hospital, Surabaya. Forty isolates of Candida albicans and Candida non-albicans were included. The isolates were tested for antifungal activity using the well diffusion and microdilution method for nystatin 1000 IU and EGCG 1.25%. Result: Diffusion test results showed a greater inhibition zone for nystatin against all analyzed Candida strains with an average diameter for Candida albicans formed by EGCG of 2.15 mm and 7.4 mm for Candida non-albicans. Meanwhile, based on the microdilution test, EGCG was better than nystatin towards all analyzed Candida strains. This study showed EGCG Minimum Fungicidal Concentration (MFC) as high as 50% (p < 0.05). Conclusion: Nystatin antifungal activity was better than EGCG supported by a greater inhibition zone in the well diffusion method. However, the antifungal activity of EGCG was better than nystatin based on microdilution methods.